Impact of urinary incontinence on medical rehabilitation inpatients. Issue 1 (16th October 2015) - Mallinson, Trudy; Fitzgerald, Colleen M.; Neville, Cynthia E.; Almagor, Orit; Manheim, Larry; Deutsch, Anne; Heinemann, Allen
Abstract : Aims: To determine the prevalence of urinary incontinence (UI) and its association with rehabilitation outcomes in patients receiving inpatient medical rehabilitation in the United States. Methods: A retrospective, cohort study of 425, 547 Medicare patients discharged from inpatient rehabilitation facilities (IRFs) in 2005. We examined prevalence of UI at admission and discharge for 5 impairment groups. We examined the impact of demographics, health, and functional status on the primary outcome, change in continence status, and secondary outcomes of discharge location and 6‐month mortality. Results: Approximately one‐quarter (26.6%) of men were incontinent at admission compared to 22.2% of women. In all diagnostic groups, continence status remains largely unchanged from admission to discharge. Patients who are older, have cognitive difficulties, less functional improvement, and longer lengths of stay (LOS), are more likely to remain incontinent, compared to those who improved, after controlling for patient factors and clinical variables. UI was significantly associated with discharge to another post‐acute setting (PAC). For orthopedic patients, UI was associated with a 71% increase in the likelihood of discharge to an institutional setting after controlling for patient factors and clinical variables. UI was not associated with death at 6 months post‐discharge. Conclusions: UI is highly prevalent in IRF patients and is associated with increased likelihood of discharge to institutional care, particularly for orthopedic patients. Greater attention to identifying and treating UI in IRF patients may reduce medical expenditures and improve other outcomes. Neurourol. Urodynam. 36:176–183, 2017 . © 2015 Wiley Periodicals, Inc.